The role and place of international law in the legal system of Kazakhstan - Shengelbayev, B.R. (Bulletin of the Karaganda University “Law Series”, 2022)
The article researches theoretical issues in the relationship between international and domestic law and offers a number of practical recommendations for consideration to increase the role of the science of international law in the implementation of Kazakhstan’s foreign policy. After a comparative legal analysis of the legislation of the Republic of Kazakhstan and the law implementation practice of some European states, the author oncludes that the country’s position in relation to international law requires adjustment, namely the transition from dualism to monism — a system used in established national legal systems of modernity after the First World War. Given the growing role of international law in Kazakhstan, it is recommended to abolish the optionality of the discipline “Public International Law” in the law schools of the country and transfer the subject to the number of mandatory ones. The author is also convinced that his proposals to create a specialized Council of International Law at the Ministry of Foreign Affairs of the Republic of Kazakhstan, as well as work within the framework of the renewed National Academy of Sciences with state status in terms of fundamental research on international legal issues, will bring practical benefits to the country while protecting national interests.